TRADE LIBERALIZATION AND FOOD SECURITY (International Journal of Food and Nutritional Sciences, 2022)
The paper assesses the intricate interplay between trade liberalization and food security—the two fundamental and critical issues in the context of globalization and rising food insecurity. Trade liberalization the reduction or elimination of tariffs, quotas, and other barriers has been promoted as an instrument for enhancing food availability, access, utilization, and stability. Through market efficiency and diversification of food sources, it promises to overall improve food security.